2012
DOI: 10.1158/1535-7163.mct-12-0100
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-29b Suppresses Prostate Cancer Metastasis by Regulating Epithelial–Mesenchymal Transition Signaling

Abstract: Prostate cancer remains the second leading cause of cancer deaths among American men. Early diagnosis increases survival rate in patients; however, treatments for advanced disease are limited to hormone ablation techniques and palliative care. Thus, new methods of treatment are necessary for inhibiting prostate cancer disease progression. Here, we have shown that miRNA-29b (miR-29b) expression was lower in prostate cancer cells (PC3 and LNCaP) as compared with immortalized prostate epithelial cells. Between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(140 citation statements)
references
References 33 publications
5
134
0
1
Order By: Relevance
“…51 MicroRNA-29b (miR-29b) is lower in prostate cancer cells and tissue as compared with normal epithelial cells, and its overexpression in PC3 prostate cancer cells decreased Snail, Twist and N-cadherin levels, while E-cadherin levels was increased. 52 LIV-1, a zinc transporter protein has been shown to induce EMT by increasing Snail, MMP-2 and -9 activation which results in shedding of heparin binding-epidermal growth factor (HB-EGF). 53 This leads to constitutive phosphorylation of epidermal growth factor receptor (EGFR) and subsequent ERK signaling leading to increased prostate cancer metastasis to bone and soft tissue.…”
Section: Snail Expression and Regulationmentioning
confidence: 99%
“…51 MicroRNA-29b (miR-29b) is lower in prostate cancer cells and tissue as compared with normal epithelial cells, and its overexpression in PC3 prostate cancer cells decreased Snail, Twist and N-cadherin levels, while E-cadherin levels was increased. 52 LIV-1, a zinc transporter protein has been shown to induce EMT by increasing Snail, MMP-2 and -9 activation which results in shedding of heparin binding-epidermal growth factor (HB-EGF). 53 This leads to constitutive phosphorylation of epidermal growth factor receptor (EGFR) and subsequent ERK signaling leading to increased prostate cancer metastasis to bone and soft tissue.…”
Section: Snail Expression and Regulationmentioning
confidence: 99%
“…Up to now, more than 50 miRNAs are abnormally expressed, leading to alteration in the expression and activity of their targets in PCa, such as miR-21, miR-320, miR-29b and miR34c (Ribas et al, 2009;Hagman et al, 2010;Hsieh et al, 2012;Ru et al, 2012 all prostate carcinoma samples compared with the BPH samples (Porkka et al, 2007;Watahiki et al, 2011). Several studies showed that the potential functions of miR-497 in human breast cancer (Li et al, 2011;Shen et al, 2012), neuroblastoma (Yadav et al, 2011), cervical cancer (Zheng et al, 2012), gastric cancer (Zhu et al, 2012) and colorectal cancer (Guo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In accord with these data, miR-29b directly targets site in the 3'UTR of snail to inhibit tumor metastasis in prostate cancer cells. Consistently, exogenous expression of miR-29b inhibits Mcl-1 and MMP-2 protein expression, and affects metastatic cascade including tumor invasion, motility, cellular survival, and proliferation (Ru et al, 2012). Tiam1, overexpressed in CRC, was validated as a target of miR-29b by binding directly in the Tiam1 3'UTR.…”
Section: Inhibiting Tumor Invasion and Metastasismentioning
confidence: 87%